Ty skyndar iag mig tijt - Valborg Lindgärde (Svensk Teologisk Kvartalskrift, 2025)
The Passion of Jesus was once a central theme for versified meditations, even in the Swedish language, and according to preserved book auction catalogues, these were found in many libraries. In the 1720s, two longer passion poems were published, written by Sophia Elisabet Brenner and Jacob Frese. The latter clearly used Haquin Spegel's recently printed passion sermons as a resource, while Brenner wrote with greater proximity to authors like Johann Gerhard. In these poems, the suffering and death of Jesus are depicted with an "I" present in the scene – a witness who actively observes and contemplates what is happening. Such poems can serve as examples of a piety characterized by introspection and individualization. But are these poems also examples of what the German hymnologist Lukas Lorbeer identifies as the era's "Personalisierung"? It is doubtful. Here, an almost anonymous "I" establishes a connection with later readers, inviting us to follow along and see what is happening. However, a proposal is presented in this article for an interdisciplinary research project based on this early modern interest in the individual, manifested in, among other things, biographies in funeral sermons, the rich occasional poetry, numerous copperplate portraits, and a frequent use of acrostics.